Perfilamento de metabólitos secundários, prospecção química e estudos quimiotaxonômicos de fungos endófitos - Lucas Magalhaes de Abreu (2010)
Secondary metabolites production by fungal endophytes was investigated in two sets of experiments. In the first one, a collection of 56 strains belonging to two morphologically similar genera, Phomopsis and Cytospora, was cultivated and submitted to micro-scale extraction of metabolites followed by metabolite profiling using HPLC-DAD and LC-MS. Detected metabolites were defined by their retention index and UV spectra, and the profiles obtained were used to classify the fungal strains in chemotypes. High resolution mass spectrometry data were used for dereplication of the major metabolites characteristic of each chemotype. Thirty eight strains were grouped in five distinct chemotypes; five strains produced unique metabolite profiles and were not classified in chemotypes. Thirteen fungi did not produced detectable amounts ofmetabolites. The strain Cytospora sp. fel 302, from chemotype 5, was cultivated in larger scale and its crude extract was chromatographed followed by the purification of the major metabolites. Fourteen metabolites were purified, including the known compounds cytosporones B, C, D, E, dothiorelones A, B, C, H, and new compounds cytosporones O, P and Q. Three metabolites were not fully identified and received the trivial names yellow 1, yellow 2 and red. Multivariate statistical analysis of classification was performed with data derived from the metabolite profiling, and the results confirmed the classification of the investigated strains into five chemotypes. In a second group of experiments, the crude extracts of a collection of 36 fungal endophytes belonging to different species were screened for bioactivity against chronic lymphocytic leukemia cells. Twenty one extracts were toxic to leukemia cells in minimum inhibitory concentrations ranging from 50 to 6.25 mg/200 mL of cell suspension. The extract of strain Libertella sp. cml 1671 inhibited leukemia cells in a concentration of 24.4 ng/200 mL. This fungus was cultivated in larger scale and part of the crude extract was micro-fractionated by semipreparative HPLC. Ninety six fractions (1.25 mL each) were collected and submitted to cytotoxicity bioassays againstleukemia cells, and fraction number 54 was detected as the most active one. LC-MS followed by metabolite dereplication identified one major compound in fraction 54, and its calculated molecular formula corresponded to those of the cytochalasins scoparasin A and phenochalasin B. The remaining extract was chromatographed and threemetabolites containing the same molecular formula as the major compound of the bioactive fraction 54 were purified: scoparasin A, phenochalasin B, and the D6,12 isomer of scoparasin A. Further bioassays will be conducted to identify which compounds are responsible for the cytotoxic effect against leukemia cells.